Investigation study of face mask consumption in Malaysia and its impact on environment - Low Chung-Yu; Bee Soo-Tueen; Law Yung-Siang; Lee Tin-Sin; Bee Soo-Ling (E3S Web of Conferences)
Although face masks might protect us against the COVID-19 virus, inappropriate disposal of used face mask can have a negative impact on the environment. As a result, it is critical to analyse the consumption of face masks and its Life Cycle Assessment to explore the environmental consequences for long-term development. In this study, the observation on the consumption of face masks have been divided into 2 periods of time, which were the period of March 2019 to March 2020 (before COVID-19 epidemic) and the period of April 2020 to April 2021 (during COVID-19 epidemic). Malaysia is estimated to consume 8,398,943 pieces of face masks per month before the COVID-19 epidemic and 62,992,074 pieces of face masks per month during the COVID-19 epidemic. Life Cycle Assessment (LCA) is carried out in this work to investigate the environmental impacts of both period of time by assessing the input and output of the face masks in a cradle-to-grave manner. OpenLCA software were used by adapting consequential system model based on ReCiPe 2016 (H) method as impact assessment method. In overall, RFL washable face mask is found to provide a lower environmental impact when compared to 3-ply surgical face mask in terms of the ReCiPe midpoint and endpoint indicator, which included Global Warming Potential, Photochemical Oxidant Formation Potential, Toxicity Potential, Ecosystem Quality, Human Health and Resource Depletion.